Improving approaches in psychotherapy and domestic violence interventions for perpetrators from marginalized ethnic groups - Turhan, Zeynep; Turhan, Zeynep (Elsevier, 2020)
The major goal of this paper is to review the existing therapeutic approaches in domestic violence perpetrator interventions by illustrating their effectiveness in reducing and ending the violent behaviour of men from marginalized ethnic groups. The paper aims to discuss how services can efficiently respond to historically marginalized ethnic perpetrators' needs and circumstances based on their social and cultural contexts. This article reviews literature about the success of domestic violence intervention approaches among marginalized ethnic group perpetrators. While each intervention approach highlights key practices for revealing violent behaviour, the combination of integrative approaches and culturally-sensitive strategies appear to be more effective for perpetrators from diverse ethnic and religious backgrounds. This article contributes to debates about culturally-sensitive approaches by discussing the importance of professionals' skills for enhancing marginalized ethnic perpetrators' motivations to remain engaged in the intervention process. It recommends a number of key culturally-specific strategies for this purpose.
Keywords: Culturally-sensitive strategies; Intervention approaches; Marginalized ethnic perpetrators; Violent behaviour; Kültüre duyarlı stratejiler; Müdahale yaklaşımları; Ötekileştirilmiş etnik failler; Şiddet içeren davranışlar